156k views
2 votes
Rewrite in simplest radical formForm for question 4 Show each step of your process.

Rewrite in simplest radical formForm for question 4 Show each step of your process-example-1
User Gyuzal
by
5.3k points

1 Answer

2 votes

Step 1:

Write the expression


\frac{x^{(5)/(6)}}{x^{(1)/(6)}}

Step 2:

Apply the division law of exponent


M^b\text{ }/ M^h=M^{b-h^{}}

Step 3:


\begin{gathered} x^{(5)/(6)}\text{ }/ x^{(1)/(6)}=x^{(5)/(6)-(1)/(6)} \\ \\ =x^{(5-1)/(6)} \\ =x^{(4)/(6)} \\ =x^{(2)/(3)} \\ =\text{ }\sqrt[3]{x^2} \end{gathered}

Final answer

User Peuhse
by
4.4k points